Three-Dimensional Radar image overlaid on a photograph - Sabiers, Richard (Cranfield University, 2020)
This picture is important because it allows you to visually gain an understanding of how an object may be interpreted by radar. A single high-resolution photographic image taken of an object and the resulting 3D radar image generated from the model. A synthetic aperture radar (SAR) volumetric image of a target was formed with Cranfield’s mini-GBSAR scanner, then overlaid over the target’s photograph. This shows a visual representation of backscattered electromagnetic waves. By comparing the representation against the original, a better understanding of the radar features is attained. This relates to my work on understanding radar object characteristics for classification using machine learning techniques.
Keywords: SAR; Bistatic; Reconstruction; DSDS19; DSDS19 Digital Image; Image Processing; Photogrammetry and Remote Sensing